Uppity women of ancient times - León, Vicki (Conari Press, 1995)
The latest volume in the Wild Women series presents vignettes about women of the ancient world in Babylon, Mesopotamia, Egypt, North Africa, Asia Minor, the Holy Land, Greece, Rome, and the western provinces.